Classification of Two Class Motor Imagery Tasks Using Hybrid GA-PSO Based K-Means Clustering. (20th April 2015) - Suraj,; Tiwari, Purnendu; Ghosh, Subhojit; Sinha, Rakesh Kumar
Abstract : Transferring the brain computer interface (BCI) from laboratory condition to meet the real world application needs BCI to be applied asynchronously without any time constraint. High level of dynamism in the electroencephalogram (EEG) signal reasons us to look toward evolutionary algorithm (EA). Motivated by these two facts, in this work a hybrid GA-PSO basedK -means clustering technique has been used to distinguish two class motor imagery (MI) tasks. The proposed hybrid GA-PSO basedK -means clustering is found to outperform genetic algorithm (GA) and particle swarm optimization (PSO) basedK -means clustering techniques in terms of both accuracy and execution time. The lesser execution time of hybrid GA-PSO technique makes it suitable for real time BCI application. Time frequency representation (TFR) techniques have been used to extract the feature of the signal under investigation. TFRs based features are extracted and relying on the concept of event related synchronization (ERD) and desynchronization (ERD) feature vector is formed.